2021
DOI: 10.1093/rheumatology/keab339
|View full text |Cite
|
Sign up to set email alerts
|

Intensive and app-delivered occupational therapy to improve upper extremity function in early diffuse cutaneous systemic sclerosis: a pilot two-arm trial

Abstract: Objective Systemic sclerosis (SSc) reduces upper extremity function and performance of everyday activities; however, there are few evidence-based rehabilitation interventions. This study examined short and longer-term effects of two occupational therapy interventions on hand disability. Methods Participants with diffuse cutaneous SSc were randomized to one of two 18-week interventions: Intensive group, receiving 8-weekly in-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The study types were as follows: case study ( n = 2), experimental ( n = 2), formative evaluation ( n = 1), narrative ( n = 1), randomized controlled trial (RCT: n = 4). The review team (SW, EE, LM, SS) organized and identified the themes of the 10 articles: Cognition (Perkins et al, 2022); Environment/Home Modifications (Breeden, 2016); Health Management (Scriven et al, 2019); Occupational Engagement (Laver et al, 2020); and Performance-Based intervention (Boehm et al, 2015; Lafaro et al, 2020; Murphy et al, 2021; Perkins et al, 2022; Plow et al, 2019; Sclarsky & Kumar, 2021). Two of the studies were published in the American Journal of Occupational Therapy (Boehm et al, 2015; Sclarsky & Kumar, 2021), and one in a rehabilitative journal (Plow et al, 2019); two within aging-specific journals (Laver et al, 2020; Perkins et al, 2022); four within health-specific journals (Beit Yosef et al, 2022; Lafaro et al, 2020; Murphy et al, 2021; Scriven et al, 2019), and one in a technology-specific journal (Breeden, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study types were as follows: case study ( n = 2), experimental ( n = 2), formative evaluation ( n = 1), narrative ( n = 1), randomized controlled trial (RCT: n = 4). The review team (SW, EE, LM, SS) organized and identified the themes of the 10 articles: Cognition (Perkins et al, 2022); Environment/Home Modifications (Breeden, 2016); Health Management (Scriven et al, 2019); Occupational Engagement (Laver et al, 2020); and Performance-Based intervention (Boehm et al, 2015; Lafaro et al, 2020; Murphy et al, 2021; Perkins et al, 2022; Plow et al, 2019; Sclarsky & Kumar, 2021). Two of the studies were published in the American Journal of Occupational Therapy (Boehm et al, 2015; Sclarsky & Kumar, 2021), and one in a rehabilitative journal (Plow et al, 2019); two within aging-specific journals (Laver et al, 2020; Perkins et al, 2022); four within health-specific journals (Beit Yosef et al, 2022; Lafaro et al, 2020; Murphy et al, 2021; Scriven et al, 2019), and one in a technology-specific journal (Breeden, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The tele-CO–OP group showed greater improvement in their Canadian Occupational Performance Measure (COPM; Law et al, 1990) performance and satisfaction scores than the waitlist control group participants (Beit Yosef et al, 2022). Second, the Murphy et al (2021) study investigated the Rehabilitation for Arm Coordination and Hand (REACH; Murphy et al, 2018) EB upper extremity intervention with App-delivered home exercises (intensive group) and occupational therapy sessions, compared to App-delivered home exercise only (telehealth group) for individuals with scleroderma ( N = 32). Participants completed weekly 45- to 60-minute sessions over 7 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Non-pharmacological management of connective tissue diseases (CTDs) may be invasive and non-invasive, and includes, but is not limited to patient education,9 self-management,10 physical exercise,11 lifestyle or behaviour interventions (eg, photoprotection or smoking cessation),12 13 psychological counselling,14 cognitive behavioural therapy,15 relaxation or yoga,16 17 dietary, nutritional or microbiome interventions,18 19 stretching,20 massage,21 hand and foot interventions, assistive technology and devices,22 mouth exercise therapy,23 dental health and hygiene,24 modalities such as paraffin baths,25 shockwave therapy,26 acupuncture27 and transcutaneous electrical nerve stimulation,28 hydrotherapy and manual lymph drainage (MLD) 29. Furthermore, it may include skin and wound care, ulcer management (eg, debridement),30 minor surgical procedures such as calcinosis removal and detection and management of malnutrition 31…”
Section: Methodsmentioning
confidence: 99%
“…Ideally, all patients with early dcSSc should be assessed by an occupational therapist, as almost all patients have considerable functional disability, including impairment of hand function 12 . ‘Remote’ occupational therapy via a mobile app 81 could be a way forward, at least in some patients.…”
Section: Best-practice Managementmentioning
confidence: 99%